Pelatihan Penulisan Esai Opini dan Mentoring Studi Lanjut bagi Pendidik Perempuan Indonesia - Risa Fitria; Grace Amialia Anfetonanda; Ika Kana Trisnawati (Jurnal Pelayanan dan Pengabdian Masyarakat (Pamas), 2023)
This Community Service aims to help enhance the writing skills of female educators and help them prepare the documents needed for further studies. For this reason, female educators such as lecturers and teachers from various regions in Indonesia were invited to attend virtual tutoring through the Zoom platform. This training and mentoring activities were carried out in several meetings and delivered by several resource persons regarding the techniques of writing opinion essays and supporting documents such as study objective and personal statement, needed to continue studies, especially at foreign universities. Nevertheless, despite having received a positive response from the participants, this training was still limited only to the introduction of opinion essays and structure in essay writing and only concerned with writing study objective and personal statement. Therefore, the recommendation for the following programs is providing training that discusses other types of essays on the IELTS test and other skills needed to improve the English competence of Indonesian female educators. In addition, other writing workshops for female educators are also necessary for postgraduate studies in the future. Keywords: Postgraduate Studies Mentoring, Female Educators, Opinion Essay Writing